Chapter Application of statistical analysis to estimate the costal hazard. A case study in Liguria region - Salmona, Paola (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Liguria Region is totally exposed to the action of the sea storms and too the natural evolution of the profile of the shoreline. The phenomenon of coastal flood produces a direct damage represented by the loss of soil and an indirect damage correlated to the impact on tourism activity, social aspects and damage to heritage buildings. In recent years another type of damage source must be considered, and this is the phenomenon of the increasing of the mean sea water level, known as Sea Level Rise (SLR).